(untitled) (Damu Journal of Sport Sciences, 2024)
This study examined job justice among physical education teachers, measuring the level of job justice. Management is the umbrella term encompassing organization and job justice. Management designs the organizational structure and determines procedures and policies that ensure job justice. Effective organization contributes to achieving job justice by defining responsibilities and authorities, clarifying procedures, and providing effective communication channels. The importance of this study lies in its understanding of the most important concepts of justice among employees in an interconnected and integrated organization, which is considered one of the most important factors for the success of organizations in the modern era. Organizations must focus on developing and effectively applying these concepts to achieve their goals and remain competitive among employees. This includes fulfilling desires, working diligently, avoiding job performance leakage, and completing the required work to achieve the desired and established goals. The research aims to: 1-Design and construct a job justice scale for physical education teachers in Dhi Qar Governorate. 2-Measure the level of job justice among physical education teachers in Dhi Qar Governorate. The researcher used a descriptive survey approach due to its suitability for the nature of the current study. The nature of the phenomenon and the established objectives require the researcher to choose an appropriate approach. The research sample was intentionally selected, comprising (400) physical education teachers in Dhi Qar Governorate, representing 100% of the sample. The researcher selected samples from the research community in accordance with the main steps to solve the research problem, such as the exploratory sample, the construction sample, and the main application sample.